Gut microbiota contributes to lignocellulose deconstruction and nitrogen fixation of the larva of Apriona swainsoni - Zhang, Lei; Zhuang, Tian; Hu, Mengxue; Liu, Shuwen; Wu, Daqiang; Ji, Baozhong (Frontiers in Physiology, 2022)
Apriona swainsoni is a vital forest pest prevalent in China. The larvae of A. swainsoni live solely in the branches of trees and rely entirely on the xylem for nutrition. However, there is still a lack of in-depth research on the gut microbiota's use of almost nitrogen-free wood components to provide bio-organic macromolecular components needed for their growth. Thus, in this study, the metagenome, metaproteome, and metabolome of the A. swainsoni larvae in four gut segments (foregut; midgut; anterior hindgut; posterior hindgut) were analyzed by the multi-omics combined technology, to explore the metabolic utilization mechanism of the corresponding gut microbiota of A. swainsoni. Firstly, we found that the metagenome of different gut segments was not significantly different in general, but there were different combinations of dominant bacteria and genes in different gut segments, and the metaproteome and metabolome of four gut segments were significantly different in general. Secondly, the multi-omics results showed that there were significant gradient differences in the contents of cellulose and hemicellulose in different segments of A. swainsoni, and the expression of corresponding metabolic proteins was the highest in the midgut, suggesting the metabolic characteristics of these lignocellulose components in A. swainsoni gut segments. Finally, we found that the C/N ratio of woody food was significantly lower than that of frass, and metagenomic results showed that nitrogen fixation genes mainly existed in the foregut and two hindgut segments. The expression of the key nitrogen fixing gene nifH occurred in two hindgut parts, indicating the feature of nitrogen fixation of A. swainsoni. In conclusion, our results provide direct evidence that the larvae of A. swainsoni can adapt to the relatively harsh niche conditions through the highly organized gut microbiome in four gut segments, and may play a major role in their growth.